Effective ignition energy for capacitor short-circuit discharge in explosive environments - Dangshu, Wang; Likang, Yang; Liu, Shulin; Wang, Xinxia; Luwen, Song; Fengjuan, Wu (Frontiers in Physics, 2024)
Capacitors short-circuit discharge in an explosive environment can ignite and detonate the surrounding explosive media, causing dangerous accidents. At low voltages, this kind of discharge constitutes a micro-nano discharge; because the discharge gaps here are of the order of only microns to nanometers, the discharge process, electrode energy consumption, explosive media ignition energy, and other energy relationships are unclear. To study the relationships between the capacitor storage energy and various kinds of dissipation energies under short-circuit discharge, a model comprising conical and spherical cylinder microbumps is proposed based on the cathode surface morphology obtained by three-dimensional profiling and scanning electron microscopy, respectively. Then, the second-order non-chi-squared differential equations were established based on the principle of energy conservation and heat balance to deduce the relationships between the cathode surface temperature and height of the microbump, conical angle, and spherical radius; further, the energy consumed by the anode surface is calculated based on the theory of heat transfer. Using heat conduction theory, the energy consumed by the microbumps on the cathode surface is calculated, and the energy consumed on the anode surface is deduced using the surface heat source as the loading heat source. The residual energy of the capacitor is calculated from the discharge time and voltages before and after discharge, and the effective energy of the gas is calculated using the law of conservation of energy. Finally, the discharge channel energy, electrode energy consumption, and end residual energy of the discharge capacitor are used to derive the effective ignition energy of the explosive gas. This research is of great significance for the design of intrinsically safe circuits with high power.